TAX HOLIDAY AND INDUSTRIAL GROWTH IN SUB – SAHARAN AFRICA: A STUDY OF SELECTED SMES IN NIGERIA (Journal of Global Accounting, 2023)
This study assessed the impact of tax holiday on industrial growth of Sub-Sahara African States using selected small and medium enterprises in Nigeria as case studies. The study adopts an explanatory non-experimental research design. The data were obtained from Federal Inland Revenue Services (FIRS). A linear model of Tax Internal Revenue, VAT and Economic Growth, proxied by GDP, was estimated using the Multiple Regression technique. The result, amongst others, indicate positive effect of tax holiday on industrial growth, suggesting that increasing tax holidays to productive and priority sectors of African economy will increase the continent’s gross domestic products. It was therefore recommended that Sub-Sahara African States should grant more incentives to those sectors and monitor closely the administration of such incentives through special parastatals so as to generate relevant financial data of the actual amount of incentives relative to the economic growth regularly to evaluate the efficiency of tax incentives in the economy.
Keywords: Tax Holiday, Industrial Growth; Sub-Saharan Africa; SMEs.